2020
DOI: 10.48550/arxiv.2008.11681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex Modulation of Rapidly Rotating Young M Dwarfs: Adding Pieces to the Puzzle

Abstract: New sets of young M dwarfs with complex, sharp-peaked, and strictly periodic photometric modulations have recently been discovered with Kepler/K2 and TESS data. All of these targets are part of young star-forming associations. Suggested explanations range from accretion of dust disks to corotating clouds of material to stellar spots getting periodically occulted by spin-orbit-misaligned dust disks. Here we provide a comprehensive overview of all aspects of these hypotheses, and add more observational constrain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Stars observed in the southern continuous viewing zone (SCVZ), however, have a combined observing baseline of ∼2 yr from the 13 southern hemisphere observing sectors and extended mission observations. Although the combined baseline of these observations should enable studies of rotation signals that span multiple TESS observing sectors, attempts at measuring rotation periods longer than the length of a single sector (27.4 days) have been unsuccessful with standard rotation period measurement methods (e.g., Günther et al 2020;Martins et al 2020), although there has been some success with machine-learning-based methods of extracting rotation signals (e.g., with neural networks; Lu et al 2020;Claytor et al 2022). These prior studies using traditional methods of measuring rotation periods from light curves have suggested that challenges in measuring rotation signals across multiple sectors in TESS are likely due to scattered light at the start and end of observing sectors and signals from the orbital motion of the spacecraft around Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Stars observed in the southern continuous viewing zone (SCVZ), however, have a combined observing baseline of ∼2 yr from the 13 southern hemisphere observing sectors and extended mission observations. Although the combined baseline of these observations should enable studies of rotation signals that span multiple TESS observing sectors, attempts at measuring rotation periods longer than the length of a single sector (27.4 days) have been unsuccessful with standard rotation period measurement methods (e.g., Günther et al 2020;Martins et al 2020), although there has been some success with machine-learning-based methods of extracting rotation signals (e.g., with neural networks; Lu et al 2020;Claytor et al 2022). These prior studies using traditional methods of measuring rotation periods from light curves have suggested that challenges in measuring rotation signals across multiple sectors in TESS are likely due to scattered light at the start and end of observing sectors and signals from the orbital motion of the spacecraft around Earth.…”
Section: Introductionmentioning
confidence: 99%
“…Zhan et al ( 2019) conclude the highly structured nature of the rotational modulation of UPM J0113-5939 is a result of a dusty ring surrounding the star. Currently the nature of young M dwarfs with complex, sharp peaked and periodic rotational modulation is unknown with several scenarios to explain the origins including: spots only; accreting dust disks; co-rotating clouds of material; magnetically constrained material; spots, and a spin-orbitmisaligned disk, and spots and pulsations (see Stauffer et al 2017;Günther et al 2020a;Koen 2021, for more details).…”
Section: Discussionmentioning
confidence: 99%
“…Spectral power and coherence at high-order harmonics may result from the star hosting multiple large spots or spot groups (e.g. Rodono et al 1986;Günther et al 2020;Perger et al 2021;Perugini et al 2021). In the next section, we will investigate coherent stellar signals that do not appear to be associated with the dominant rotation period, but which may be artifacts of differential rotation, giant cells, or supergranulation.…”
Section: Gj 581mentioning
confidence: 99%